Geology and lithostratigraphy of Sungai Ulu Raya, Lojing, Kelantan - Wan Zainah Wan Isa (2019)
The study area is located at the Lojing, Gua Musang which part of the south-western corner of Kelantan state and it is lies between latitude 4˚47’27” N - 4˚49’57” N and longitude 101˚46’1.5” E - 101˚48’31.8” E. This research paper is concern with the objectives to produce the geological map in the scale of 1: 25,000 and to identify the lithostratigraphy of Sungai Ulu Raya, Lojing which lies under Gua Musang Formation. Besides, the study of the lithostratigraphy can determine the depositional environment by the facies analysis. The lithology that found in the study area is the limestone, tuff with subordinate mudstone and shale, and andesite rock. The methodology of this research was done through the satellite imagery interpretation, fieldworks activities and laboratory work. The geological map was produce by using ArcGIS software and the petrographic method was conducted to determine the mineral composition of rocks. The lithostratigraphy method was carried out along the outcrop at study area to establish the parameters used to the determine the lithostratigraphy, facies associated and sedimentary structural. The interpretation is supported by the presence of sedimentary structural and the facies analysis of the lithology unit in the research area.